Violence against metropolitan bus drivers and fare collectors in Brazil - Assunção, Ada Ávila; Medeiros, Adriane Mesquita de (Revista de Saúde Pública, 2015)
OBJECTIVE To analyze the correlation between sociodemographic factors and working conditions of bus workers in a metropolitan area and violence against them.METHODS This cross-sectional study used a nonprobabilistic sample estimated according to the number of workers employed in bus companies located in three cities in the Belo Horizonte metropolitan region in 2012 (N = 17,470). Face-to-face interviews were conducted using a digital questionnaire. The factors associated with violence were analyzed in two stages using Poisson regression, according to each level. The magnitude of the association was evaluated using prevalence ratios with robust variance and a statistical significance of 5%, and 95% confidence intervals were obtained.RESULTS The study sample comprised 782 drivers and 691 fare collectors; 45.0% participants reported at least one act of violence in the workplace in the last 12 months, with passengers being predominantly responsible. The age of the bus workers was inversely associated with violence. Chronic diseases, sickness absenteeism, and working conditions were also associated with violence.CONCLUSIONS The findings on the correlation between violence and working conditions are essential for implementing prevention strategies by transportation service managers.